Transformation of Sedentary Behavior Towards a Digital Active Lifestyle Through a Design Thinking Approach in Women Of Productive Age - Candra Wahyuni; Asruria Sani Fajriah; Eri Puji Kumalasari; Erma Retnaningtyas; Miftakhur Rohmah; Nita Dwi Astikasari; Nining Istighosah; Retno Palupi Yonni Siwi; Riza Tsalatsatul Mufida; Shanty Natalia; Siti Komariyah; Ariska Nur Aisyah Putri; Mauliana Agustin (Journal of Community Engagement in Health, 2026)
The demanding daily routines of women of productive age often lead to the neglect of physical and mental health. This sedentary lifestyle is exacerbated by a lack of time and limited digital health literacy, despite high smartphone ownership. This community service initiative aimed to transform sedentary behavior into a digitally active lifestyle by enhancing health digital literacy through a Design Thinking approach. An intensive one-day Edu-Tech Workshop was conducted for 25 women in the Blabak Health Center area, Kediri. The program utilized an abridged version of the Design Thinking framework—Empathize, Define, Ideate, Prototype, and Test—focusing on the practical application of m-health tools like Google Fit and Riliv. Evaluation was performed using pre-post tests, digital skills indicators, and a 7-day remote monitoring period via WhatsApp. Initial screening revealed that 68% of participants had low digital health literacy. Post-intervention data showed a dramatic surge in health application literacy, with average scores jumping from 35.2 to 92.0. All participants (100%) successfully configured health-monitoring ecosystems on their devices. Sustainability tracking indicated that 76% of participants actively reported achieving their daily step targets, and 60% consistently utilized digital breathing exercises to manage work-related stress. The one-day intensive workshop model effectively overcomes the "double burden" time constraints faced by modern women. By demystifying technology and integrating m-health into daily routines, this approach successfully fosters a sustainable transition toward independent health management.